2013
DOI: 10.1586/ern.13.37
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-associated secondary brain tumors after conventional radiotherapy and radiosurgery

Abstract: Although there is not enough strong molecular evidence for radiation to be a causal factor for the development of secondary brain tumors, a relationship has still been found. There is a slight but significant 2-2.7% increased risk of secondary brain tumors after conventional radiotherapy. However, this risk is small and should not preclude the use of radiotherapy as an effective treatment for uncontrolled pituitary tumors. The risk of radiosurgery-associated secondary brain tumors has not been precisely determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…The mean latency period between CRT and secondary tumor development was 19.6 years for meningioma, 11 years for glioma, and 9 years for astrocytoma. In these patients there was a slight but significant 1.3-2.7% increase in actuarial risk of secondary brain tumor (390). The incidence and the actuarial risk of secondary brain tumors are not clear in patients with CD.…”
Section: Safety Of Radiotherapymentioning
confidence: 85%
“…The mean latency period between CRT and secondary tumor development was 19.6 years for meningioma, 11 years for glioma, and 9 years for astrocytoma. In these patients there was a slight but significant 1.3-2.7% increase in actuarial risk of secondary brain tumor (390). The incidence and the actuarial risk of secondary brain tumors are not clear in patients with CD.…”
Section: Safety Of Radiotherapymentioning
confidence: 85%
“…Irradiation was the standard treatment for patients with PAs until the late 1980s, when it was found that irradiation can be harmful to patients and result in an increased risk of vascular and cognitive impairment and the development of secondary tumours (21). This together with improved neurosurgical techniques may explain the low frequency of irradiation treatment in this cohort of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The mean number (range) of patients diagnosed with PAs per year was 54 (42-69); 26 (17-36) in men and 28 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) in women. The age-SIRs per 100 000 people per year are presented in Fig.…”
Section: Time Trends Of Incidencementioning
confidence: 99%
“…Debus et al [64] reported late grade 3 radiation morbidity symptoms, such as reduced vision, visual-field defect and trigeminal neuropathy, in 2.1% patients, whereas Milker-Zabel et al [20] did not report any significant acute or late grade 3 symptoms. Concerning the risk of secondary malignancies, to the best of our knowledge no case has been reported after FRT of meningiomas, however limited series have reported a long follow-up of 15-20 years, thus possibly missing radio-induced secondary cancers occurring during the long-term [72]. Long-term follow-up of IMRT patients is also required to assess whether this historic data remain comparable in view of the larger volumes of normal tissue receiving low-dose radiation with IMRT [73].…”
Section: Side Effects and Long-term Risksmentioning
confidence: 88%